The Challenges of Managing Ovarian Cancer in the Developing World - Olivier Mulisya; Franck K. Sikakulya; Mbusa Mastaki; Tambavira Gertrude; Mathe Jeff (Case Reports in Oncological Medicine)
Ovarian cancer has high morbidity and mortality rates among cancers of the reproductive system. The disease typically presents at late stage when the 5-year relative survival rate is only 29%. Similarly, access to prevention, early diagnosis, treatment, and palliative care for cancer-related disease is insufficient. The availability of cancer treatments in Africa is especially poor. Case. A 17-year-old lady, nulliparous, was admitted with complaint of abdominal swelling and loss of weight and a huge left ovarian cyst revealed by ultrasound scan. Laparotomy was done, and a mass which resembled a hemorrhagic solid tumor was found. Grossly, the left ovarian mass measured 15.0×20.0×8.0 cm and a left salpingectomy was performed. Two months later, she came back with lower limb swelling progressively increased in a week with vulvar edema, with a palpable mass. She was discharged on request by her relatives for traditional medicine. One year later, she passed on in an unrevealed picture. The management of ovarian cancer is too challenging in low-resource countries, from hospital settings to the communities with poor cancer awareness. It is therefore imperative that healthcare resources, policies, and planning focus to be coordinated in a rational way.